Desenvolvimento e morfodinâmica de praias sobre plataformas de abrasão em litorais de micromaré dominados por ondas - Souza, Brenda Silva de (2018)
Beaches on shore platforms are influenced by their singular geomorphology and respond differently from sandy beaches in terms of morphology and morphodynamic processes. The application of models has become a useful tool in the study of these complex environments. The model of Trenhaile (2004), proposed for mesotidal and macrotidal shore platform coasts, has been considered the most suitable among several models. This model considers the morphology of the shore platforms and hydrodynamic conditions of the coast. Studies about beach development on shore platforms along microtidal coasts, not frequently, consider the contribution of hydrodynamic factors. Thus, the aim of present study was to propose a new model for the development of beaches on shore platforms in microtidal coast, where waves are the fundamental morphodynamical agent. This propose was based on Trenhaile (2004) assumptions and elements. In addition, the influence of the shore platforms on the morphodynamic processes of these beaches was evaluated. The study area comprised three beaches on shore platforms located in the coast of Espírito Santo, Brazil, classified as microtidal coast. Some adaptation from Trenhaile model (2004) were applied for the success of new model: the vertical limit of emerse beach profile was obtained by wave run up during spring tidal and profile morphology data were known by field survey. The results indicated that shore platforms do not prevent the accumulation of sediments and, consequently, the formation of beaches. Although, shore platform exerts significant influence on the limitation of the accommodation space, on beach morphology and morphodynamic processes. In general, the new model was able to represent the morphology and the sediment accommodation capacity of the studied beach systems.